Associations between obesity and arterial stiffness assessed by cardio-ankle vascular index in healthy children and adolescents - Horikoshi, Yuko; Sakuraba-Hirata, Rie; Suzuki, Nina; Inomata, Yuki; Oikawa, Moe; Kotani, Toa; Watanabe, Takumu; Takahashi, Eri; Okazaki, Kanako; Hoshi, Masayuki; Endo, Yasuhiro; Nakanowatari, Tatsuya; et al. (Frontiers in Cardiovascular Medicine, 2025)
AimsCardio-ankle vascular index (CAVI) is a non-invasive method for evaluating arterial stiffness. In adults, CAVI has been reported to show negative correlation with body mass index (BMI) known as the “obesity paradox”; however, whether this also applies to children remains unclear. In addition, childhood obesity is a problem in developed countries, and the utility of CAVI in children has not yet been clarified. We here aimed to clarify the relationship between obesity parameters and CAVI in healthy children.MethodsThis was a cross-sectional study conducted in 2024. We evaluated CAVI and its associated factors in 590 children aged 6–15 years (mean age: 10.5 years, 51.0% female). Additionally, obesity parameters, including the Rohrer index, percentage of overweight (POW), body fat percentage and body fat mass determined by bioelectrical impedance analysis, and BMI were assessed. The participants were categorized into groups based on the obesity parameters.ResultsCAVI decreased as obesity level increased, showing the lowest CAVI in the highest obesity category. CAVI was positively correlated with age (R = 0.18, p < 0.05), and was negatively correlated with Rohrer index, body fat percentage, body fat mass, POW, BMI, and heart rate, (R = −0.33, R = −0.23, R = −0.14, R = −0.30, R = −0.19, R = −0.14, respectively; p < 0.01 for all). In contrast, CAVI showed no significant correlation with blood pressure or body weight. Furthermore, multiple linear regression analyses after adjusting for possible obesity-related factors including age, sex, blood pressure, and heart rate, showed that all obesity parameters were independent predictors of CAVI.ConclusionObesity parameters are negatively and independently associated with CAVI in healthy children.